C-reactive protein as a prognostic indicator for rebleeding in patients with nonvariceal upper gastrointestinal bleeding. Issue 5 (May 2015) - Lee, Han Hee; Park, Jae Myung; Lee, Soon-Wook; Kang, Seung Hun; Lim, Chul-Hyun; Cho, Yu Kyung; Lee, Bo-In; Lee, In Seok; Kim, Sang Woo; Choi, Myung-Gyu
Abstract: Background: In patients with acute nonvariceal upper gastrointestinal bleeding, rebleeding after an initial treatment is observed in 10–20% and is associated with mortality. Aim: To investigate whether the initial serum C-reactive protein level could predict the risk of rebleeding in patients with acute nonvariceal upper gastrointestinal bleeding. Methods: This was a retrospective study using prospectively collected data for upper gastrointestinal bleeding. Initial clinical characteristics, endoscopic features, and C-reactive protein levels were compared between those with and without 30-day rebleeding. Results: A total of 453 patients were included (mean age, 62 years; male, 70.9%). The incidence of 30-day rebleeding was 15.9%. The mean serum C-reactive protein level was significantly higher in these patients than in those without rebleeding ( P  < 0.001). The area under the receiver operating characteristics curve with a cutoff value of 0.5 mg/dL was 0.689 ( P  < 0.001). High serum C-reactive protein level (odds ratio, 2.98; confidence interval, 1.65–5.40) was independently associated with the 30-day rebleeding risk after adjustment for the main confounding risk factors, including age, blood pressure, and initial haemoglobin level. Conclusions: The serum C-reactive protein was an independent risk factor for 30-day rebleeding in patients with acute nonvariceal upper gastrointestinal bleeding, indicating a possible role as a useful screening indicator for predicting the risk of rebleeding.